Aplicación de contabilidad por el sistema de inventario permanente en “Almacén Plastibana”, ubicado en la provincia de el Guayas, cantón El Triunfo: periodo agosto 2014 - Rubianes Freire, Silvia Ruth (2015)
The present research work entitled "application of accounting system of permanent inventory in"StorePlastibana", located in the province of Guayas, The Triunfo Canton: period August 2014, held to comply with one of the requirements established in the academic regulations of the National University of Loja, mode of studies distance, race of accounting and auditing. The goals arrived to meet through the development of the accounting process, starting with the preparation of the Plan and accounts Manual according to the needs of the company, then by the physical observation of the commercial documents identified assets, rights and obligations of the business premises; managed to structure in their respective Cardex cards for which the weighted average method was applied allowing control of the inputs and outputs of items from the store, finally by the memorandum of operations is gave way to the record of commercial transactions in the journal book, then to the ledger, Trial Balance, auxiliary books and finally executed the State of Results Financial Status, cash flow and statement of changes in equity. As conclusion at the end of the application of the system of permanent inventory accounting was to determine usefulness in the study period; result that was known to the owner of the company together with the accomplished process, event that reflected in the owner a panorama that is clear about the correct process in bookkeeping, allowing you to have a clear vision of its future objectives for decision making